Structural aspects of agonism and antagonism in the oestrogen receptor. - Pike, A; Brzozowski, A; Walton, J; Hubbard, R; Bonn, T; Gustafsson, J; Carlquist, M (2000)
We have determined the three-dimensional structures of both alpha- and beta-forms of the ligand-binding domain of the oestrogen receptor (ER) in complexes with a range of receptor agonists and antagonists. Here, we summarize how these structures provide both an understanding of the ER's distinctive pharmacophore and a rationale for its ability to bind a diverse range of chemically distinct compounds. In addition, these studies provide a unique insight into the mechanisms that underlie receptor activation, as well as providing a structural basis for the antagonist action of molecules, such as raloxifene.